The Influence of the SECI Knowledge Creation Model on Consumer New Knowledge in Digital Business Platforms: A Study of Mobile Legends Users in Surabaya - Kafah Dewantara Lawitani; R. Yuniardi Rusdianto (Danadyaksa: Post Modern Economy Journal, 2026)
Digital business platforms have transformed consumers from passive product recipients into active knowledge-creating agents. This study examines the influence of the SECI knowledge creation model Socialization, Externalization, Combination, and Internalization on new knowledge formation among Mobile Legends consumers in Surabaya, Indonesia. Employing a quantitative associative research design, data were collected from 150 active Mobile Legends users through structured Likert-scale questionnaires and analyzed using multiple linear regression. Results confirm that all four SECI dimensions simultaneously and partially influence new knowledge formation. Simultaneously, the model explains 53.6% of variance in new knowledge formation (F = 41.846, p = 0.000). Partially, Combination emerges as the strongest predictor (β = 0.325), followed by Internalization (β = 0.317), Socialization (β = 0.227), and Externalization (β = 0.154), all significant at p < 0.05. These findings extend the SECI model and Knowledge-Based View beyond formal organizational settings, establishing that consumer-driven knowledge creation in non-formal digital ecosystems is a structured and measurable phenomenon. Practically, the findings provide strategic guidance for digital platform operators to invest in consumer knowledge capital as a source of sustained competitive advantage.